Two new species of Holthuisana Bott, 1969 (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from West Papua, Indonesia - Wowor, Daisy; Ng, Peter K. L. (Zootaxa, 2009)
Two new species of gecarcinucid crabs of the genus Holthuisana Bott, 1969, are described from the islands of Waigeo and Batanta in West Papua Province, Indonesia. Holthuisana lipkei n. sp. differs from the allied H. alba Holthuis, 1980, from Papua New Guinea by having fully developed pigmented eyes, smooth carapace, smooth and distinctly gaping second major chela, and the relatively more slender male first gonopod. Holthuisana tikus n. sp. resembles H. subconvexa (Roux, 1927) from Papua Province but differs by possessing indistinct and shallow epigastric lobes on the carapace, the absence of a subdistal tooth on the upper margin of the ambulatory merus of pereiopods 2-5 and a relatively stouter male first gonopod. The taxonomic status of Holthuisana and its constituent species is also discussed.